KEDUDUKAN DAN HUBUNGAN TRIUMVIRAT MENTERI SEBAGAI PELAKSANA TUGAS KEPRESIDENAN DALAM SISTEM KETATANEGARAAN DAN KEMENTERIAN NEGARA REPUBLIK INDONESIA - Saputra, Imran Eka; Razak, Furqan; Rahman, Ali; Nur, Alqadri (The Juris, 2024)
This research aims to examine the position of the triumvirate of ministers in the constitutional system of the Republic of Indonesia and examine the relationship between the triumvirate of ministers as executors of presidential duties in the State Ministry system of the Republic of Indonesia. The type of research used in this research is normative legal research. The research results show that the position of the triumvirate of ministers in the constitutional system of the Unitary State of the Republic of Indonesia has been regulated in the third amendment to the 1945 Constitution of the Republic of Indonesia, namely Article 8 paragraph (3) which regulates more detailed rules in the event that the President and Vice President are absent. Then the reason why the ministers of the Triumvirate carry out presidential duties is because they are considered to understand the ins and outs of government affairs. The solution offered by the author is that the President and the People’s Representative Council need to make derivative regulations for the implementation of Article 8 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia and a change needs to be made in Law Number 39 of 2008 concerning the Ministry of State Affairs.